'Animals Just Love You as You Are': Experiencing Kinship across the Species Barrier. (August 2014) - Charles, Nickie
This article explores how affective relationships between humans and animals are understood and experienced. It argues that, although the context of close relationships with pets has changed, affective relationships between humans and animals have a long history. The affinities between people and their pets are experienced as emotionally close, embodied and ethereal and are deeply embedded in family lives. They are understood in terms of kinship, an idiom which indicates significant and enduring connectedness between humans and animals, and are valued because of animals' differences from, as well as similarities to, humans. Kinship across the species barrier is not something new and strange, but is an everyday experience of those humans who share their domestic space with other animals. Rather than witnessing a new phenomenon of post-human families, multi-species households have been with us for a considerable length of time but have been effectively hidden from sociology by the so-called species barrier.